Comparable Attenuation of Sympathetic Nervous System Activity in Obese Subjects with Normal Glucose Tolerance, Impaired Glucose Tolerance, and Treatment Naïve Type 2 Diabetes following Equivalent Weight Loss - Straznicky, Nora E.; Grima, Mariee T.; Sari, Carolina I.; Lambert, Elisabeth A.; Phillips, Sarah E.; Eikelis, Nina; Mariani, Justin A.; Kobayashi, Daisuke; Hering, Dagmara; Dixon, John B.; Lambert, Gavin W. (Frontiers in Physiology, 2016)
Background and Purpose: Elevated sympathetic nervous system (SNS) activity is a characteristic of obesity and type 2 diabetes (T2D) that contributes to target organ damage and cardiovascular risk. In this study we examined whether baseline metabolic status influences the degree of sympathoinhibition attained following equivalent dietary weight loss. Methods: Un-medicated obese individuals categorized as normal glucose tolerant (NGT, n=15), impaired glucose tolerant (IGT, n=24) and newly-diagnosed T2D (n=15) consumed a hypocaloric diet (29% fat, 23% protein, 45% carbohydrate) for 4-months. The three groups were matched for baseline age (56 + 1 years), body mass index (BMI, 32.9 + 0.7 kg/m2) and gender. Clinical measurements included whole-body norepinephrine kinetics, muscle sympathetic nerve activity (MSNA, by microneurography), spontaneous cardiac baroreflex sensitivity (BRS) and oral glucose tolerance test. Results: Weight loss averaged -7.5 + 0.8, -8.1 + 0.5 and -8.0 + 0.9 % of body weight in NGT, IGT and T2D groups, respectively. T2D subjects had significantly greater reductions in fasting glucose, 2-h glucose and glucose area under the curve (AUC0-120) compared to NGT and IGT (group effect, P<0.001). Insulinogenic index decreased in IGT and NGT groups and increased in T2D (group x time, P=0.04). The magnitude of reduction in MSNA (-7 + 3, -8 + 4, -15 + 4 burst/100hb, respectively) and whole-body norepinephrine spillover rate (-28 + 8, -18 + 6 and -25 + 7 %, respectively), time effect both P<0.001, did not differ between groups. After adjustment for age and change in body weight, ∆ insulin AUC0-120 was independently associated with reduction in arterial norepinephrine concentration, whilst ∆ LDL-cholesterol and improvement in BRS were independently associated with decrease in MSNA. Conclusions: Equivalent weight loss through hypocaloric diet is accompanied by similar sympathoinhibition in matched obese subjects with different baseline glucose tolerance. Attenuation of hyperinsulinemia and hyperlipidemia, rather than glycemic indices, is associated with reduction in SNS activity following weight loss intervention.